Historical changes in agricultural land use in Hungary - Káposzta, József; Némediné Kollár, Kitti (Studia Mundi – Economica, 2021)
Hungary is home to natural facilities (economic geography, weather conditions, biological bases, production culture) and human resources, which provide a comparative advantage for the agricultural production over most of the European countries. In relation to the present-day Hungarian agriculture the most important question is not whether the „agriculture” serves as an engine of the modernization, but how it can adapt to the changes of the global food industry trends. The model of the so-called „sustainable agricultural development” being adapted to the Hungarian conditions, is a perspectival opportunity for both Hungarian qualities and the way of the European Union. This model combines the relations of the environmentally friendly agriculture, parts of the Western European cost intensive system (mostly in case of gardening culture), a few pieces from the North American extensive technology (primarily in the arable crop production) and the national agricultural traditions, which serve as a frame for the above mentioned. Our study tries to give an insight on how the Hungarian leasehold evolved to the age of the regime change, with the help of showing the history of the Hungarian leasehold systems.